Dampak Globalisasi Terhadap Bisnis Internasional - Feronica Simanjorang; Glenesia Angelica; Nazlina Dwi Putri; Leoni Avista Dewi; Alwi Amanda; Muhammad Musthafa Haykal (Jurnal Manajemen Riset Inovasi, 2023)
The development of international business activities coincides with the widespread phenomenon of market globalization (Cavusgil, Knight, & Riesenberger, 2008). Market globalization refers to the growing economic integration and growing interdependence of countries around the world. The purpose of writing this article is to analyze the implications of globalization for international business. The study population consists of four empirical cases: strategies of ICT producers to cope with globalization, strategies used by Brazilian companies to survive China's challenges due to globalization, strategies for globalization and corporate real estate. This method allows researchers to select cases that have the desired information or required characteristics that are useful in achieving research objectives. The internationalization of companies refers to the tendency of companies to systematically increase the international scope of their business activities, whereas globalization refers to the macrotrend-intensive economic relations between the countries of the world. Globalization is driving companies to internationalize and substantially increase the volume and type of cross-border transactions in goods, services, and capital. Also, globalization leads to the rapid spread and diffusion of products, technology and knowledge in the world. The process of globalization is a natural process which is the result of the growth and acceleration of the process of character generalization and production processes.